Changes, changes - Hutchins, Pat, 1942- (New York : Aladdin Books, 1987)
Two wooden dolls rearrange wooden building blocks to form various objects.
K-3
K-3
Wilson's Children
Elem. School Library Collection
Notable/Best Books (A.L.A.)
NP
Keywords: Toys -- Fiction; Stories without words; Toys -- Fiction; Stories without words